The Originality of the Representation of the Image of Nature in the Lyrics of Sergei Yesenin and Hamid Olimjon - Boltaeva Maxbuba Sharipovna (Researchparks Publishing, 2021)
The article reveals the aesthetic classification of the expression of nature in the lyrics of S.Yesenin, the features of artistic individuality and identifies the functions performed by the landscape in the poetry of poets. We can say that the theme of nature is revealed in almost all of Yesenin and X.Olimjon’s poems, and poets not only describe everything that surrounds them, but also compare natural phenomena with the human body